Factors Influencing Profit Sharing Financing in Islamic Rural Bank: Evidence from Indonesia - Fitria, Asyifa Zahrah; Maulana, Agus (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2025)
This study aims to examine the impact of several financial indicators, namely return on assets (ROA), capital adequacy ratio (CAR), financing to deposit ratio (FDR), non-performing financing (NPF), and operational efficiency ratio (OER), on profit sharing financing, as represented by the profit sharing ratio (PSR). The data utilized comprises annual reports sourced from Islamic Rural Banks registered with the Financial Services Authority (OJK) during the period spanning 2018 to 2020. Sample selection employed purposive sampling technique, resulting in 158 banks with total 474 data being analyzed through panel data regression analysis. The regression model was processed and tested using the STATA application. Findings reveal that (1) ROA positively influences profit sharing financing, indicating that higher ROA leads to increased distribution of profit sharing financing; (2) CAR and FDR do not significantly impact profit sharing financing; (3) NPF positively affects profit sharing financing, suggesting that higher NPF correlates with increased profit sharing financing; and (4) OER positively influences profit sharing financing, indicating that higher OER is associated with increased profit sharing financing.